68Ga-PSMA-PET/CT-directed IGRT/SBRT for oligometastases of recurrent prostate cancer after initial surgery. (1st February 2020) - Marzec, J.; Becker, J.; Paulsen, F.; Wegener, D.; Olthof, S.-C.; Pfannenberg, C.; Schwenck, J.; Bedke, J.; Stenzl, A.; Nikolaou, K.; la Fougère, C.; Zips, D.; et al.
Abstract: Background: We evaluated efficacy and toxicity of 68 Ga-PSMA-Positron Emission Tomography/Computed Tomography (PET/CT)-directed stereotactic body radiotherapy and image-guided radiotherapy (SBRT/IGRT) for oligometastases of prostate cancer recurrences after previous surgery. Methods: Nineteen patients were analyzed within a prospective PET-registry study (064/2013BO1) and retrospectively analyzed (807/2017BO2) fulfilling the following inclusion criteria: biochemical recurrence after radical prostatectomy, ≤five 68 Ga-PSMA-PET/CT positive lesions. Biochemical control was evaluated with EORTC (European Organization for Research and Treatment of Cancer)- and Phenix-definitions. Toxicity was scored according to CTCAE-criteria v. 4.03. Results: A total of 38 oligometastases (19 patients, 2 with re-treatment) were treated with SBRT/IGRT from October 2014 to July 2017. 68 Ga-PSMA-PET/CT-positive lesions were detected on average 39 months (5–139) after prostatectomy (pT2b-3b pN0-1 cM0). Mean PSA (Prostate-specific antigen)-level at time of imaging reached 2.2 ng/mL (range 0.2–10.1). PET/CT-positive lesions were treated with different fractionation schedules reaching biological equivalent doses (BED) of 116.7–230.0 Gy. Concomitant androgen deprivation therapy (ADT) was given in seven patients. After a median follow-up of 17 months (4–42) all patients were alive. Estimated 1-year PSA- control ( n  = 19) reached 80.8% (Phenix) and 67.5% (EORTC). A PSA-decline (≥50%) was detected in 16/19 patients after radiotherapy. Higher graded G3+-acute toxicity did not occur. Temporary late G3-proctitis was detected in one patient. Conclusions: Reaching of nadir ≤0.1 or 0.2 ng/mL was associated by improved DMFS (distant metastases free survival) and could serve as a surrogate endpoint for RT of oligometastases after initial prostatectomy. Short term effects of 68 Ga-PSMA-PET/CT-based ablative radiotherapy for oligometastases demonstrated an acceptable toxicity profile and favorable biochemical response.